2017
DOI: 10.1007/s12010-017-2478-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Encapsulated in Milk Exosomes Resists Human Digestion and Possesses Enhanced Intestinal Permeability in Vitro

Abstract: Exosomes, the extracellular secretary nano-vesicles, act as carriers of biomolecules to the target cells. They exhibit several attributes of an efficient drug delivery system. Curcumin, despite having numerous bioactive and therapeutic properties, has limited pharmaceutical use due to its poor water solubility, stability, and low systemic bioavailability. Hence, this study aims to enhance the therapeutic potential of curcumin, a model hydrophobic drug, by its encapsulation into milk exosomes. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 43 publications
3
130
0
1
Order By: Relevance
“…Milk EVs have been extensively studied for their biological functions upon consumption (Agrawal et al., ; Aqil et al., ; Aqil, Munagala, Jeyabalan, Agrawal, & Gupta, ; Arntz et al., ; Badawy, El‐Magd, & AlSadrah, ; Leiferman et al., ; Matsuda & Patel, ; Munagala, Aqil, Jeyabalan, & Gupta, ; Munagala et al., ; Oliveira et al., , 2017) and numerous studies have reported that milk EVs are bioaccessible (survive digestion; Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya, Rani, Onteru, & Singh, ; Vashisht, Rani, Onteru, & Singh, ) and bioavailable (Le Doare et al., ; Wang et al., ; Zempleni, ; Zempleni et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Milk EVs have been extensively studied for their biological functions upon consumption (Agrawal et al., ; Aqil et al., ; Aqil, Munagala, Jeyabalan, Agrawal, & Gupta, ; Arntz et al., ; Badawy, El‐Magd, & AlSadrah, ; Leiferman et al., ; Matsuda & Patel, ; Munagala, Aqil, Jeyabalan, & Gupta, ; Munagala et al., ; Oliveira et al., , 2017) and numerous studies have reported that milk EVs are bioaccessible (survive digestion; Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya, Rani, Onteru, & Singh, ; Vashisht, Rani, Onteru, & Singh, ) and bioavailable (Le Doare et al., ; Wang et al., ; Zempleni, ; Zempleni et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…According to more than 30 studies, from different teams around the world, milk EVs resisted in vitro digestion (Benmoussa et al., ; Kahn et al., ; Liao et al., ; Rani et al., ; Shandilya et al., ; Vashisht et al., ) were internalized by recipient cells upon co‐incubation (Admyre et al., , 2008; Aqil et al., , ; Badawy et al., ; Golan‐Gerstl et al., ; Hock et al., ; Kahn et al., ; Liao et al., ; Maburutse, Park, Oh, & Kim, ; Martin et al., ; Matsuda & Patel, ; Mobley et al., ; Munagala et al., ; Naslund et al., ; Qin et al., ; Vashisht, Rani, Onteru, & Singh, ; Yu et al., ), transduced through the intestinal wall in vitro (Rani et al., ; Shandilya et al., ; Wolf et al., ), and were detected in animal models after ingestion (Manca et al., ; Munagala et al., ) or intravenous injection (Somiya, Yoshioka, & Ochiya, ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Recent efforts have been undertaken to use milk‐derived exosomes foe the encapsulation curcumin which could enhance curcumin transport and drug effects. These results suggested that using milk‐derived exosomes containing curcumin could induce therapeutic effects of curcumin in the better way than using curcumin alone …”
Section: Introductionmentioning
confidence: 97%